Three Distances in Linquan Gaozhi - Li, Kelin (Aisthesis, 2024)
Linquan Gaozhi (《주홋멕鈴》) was completed during the North Song period, a period of full development in Chinese landscape painting. As a comprehensive work, this book encompasses various aspects of painting techniques, appreciation criteria, and artistic concepts. The concept of the “Three Distances” proposed in this book not only became an important resource in the history of painting and art criticism but also continues to play a significant role in reshaping theoretical interpretation and inspiring artistic creation among contemporary scholars and artists. By historically tracing and reconstructing the spatial arrangement of the “Three Distances (힛陶),” the interconnections and operational environment of these distances are revealed. In the visual language of landscape painting, we seek to understand the motivation of Guo Xi as a painter and his self-recognition as a literatus. Guo Xi’s dual identity brings out the complex personality of Song literati, which maintains a balance between responsibility within the world and the pursuit of essential Dao in a typical articulation.